PhD Competences in Food Studies - Gonzalez-Martinez, Chelo (2015)
In European Higher Education, learning outcomes and competences have been used sometimes with di erent meanings and sometimes with the same meaning. But both terms have been more commonly used to refer to knowledge, understanding and abilities a student must demonstrate at the end of a learning experience. Their use is a consequence of the paradigm shift of the Bologna Process to a learner centered education environment. The de nition of standards of competences (or learning outcomes) for the PhD degree is thus a need for the quality assurance of this degree. In this work, subject-speci c and generic competences for the PhD in Food Science and Technology and their alignment with the European Quali cations Framework (EQF) level descriptors for quality assurance purposes have been identi ed.